The Influence of Tax Awareness and KnowledgeAgainst the Compliance of Personal Tax Reportingwith Religiosity as an Intervening Variableat the Auliya Insan Utama Foundation - Rahmad Hidayat; beti nurbaiti; Zian Fachrian (Journal of Accounting, Business and Management (JABM), 2023)
This research was conducted with the aim to determine the direct effect between Tax Knowledge and Tax Awareness on Tax Compliance, and to determine the indirect effect of Tax Knowledge and Tax Awareness on Tax Compliance through intervening variable Religiosity. The population in this study were all employees at the Auliya Insan Utama Foundation with a saturated sampling method of 94 employees. In this study, the authors used the Structural Equation Modeling (SEM) quantitative method with the help of Lisrel 8.8 software. The test results show there is a positive relationship between Tax Awareness and Tax Knowledge on Tax Compliance, where the value of t value> 1.96. The test results also show that there is no indirect effect between Tax Awareness on Tax Compliance through intervening variable Religiosity, but there is an indirect effect between Tax Knowledge on Tax Compliance through intervening variable Religiosity.